Development of sustainability in public sector procurement. Issue 6 (19th September 2017) - Gelderman, Cees J.; Semeijn, Janjaap; Vluggen, Rob
Abstract : Public organizations are increasingly adding environmental and social aspects in their strategic agendas. This paper focuses on the actors and factors that influence the speed of implementation of sustainability initiatives. Four healthcare organizations in The Netherlands were studied. Semi-structured interviews were conducted with top management, budget owners and procurement professionals. Although top management assigned strategic importance to sustainability initiatives, budget owners had the final say in implementation. Procurement professionals had very little influence on the implementation process of sustainability.